A Review of Antidiabetic Activity of Bauhinia purpurea plant and its Phytochemical Constituents - Tavamani Balan; Yushanani Yusari; Laavanya Rajendhiran; Nur Ainina Hani Ghazali; Suganya Murugesu; Sharon Fatinathan; Zainul Amiruddin Zakaria; Charles Gnanaraj; Mohd Hijaz Mohd Sani; Vikneswari Perumal (Asian Journal of Medicine & Health Sciences, 2023)
Plant Bauhinia purpurea L. (Caesalpinioideae), known as ‘‘tapak kuda’’ in Malay, has been reported for its therapeutic value from various parts of the plant supported by various scientific evidence. The objective of this narration is to assemble all data and information associated with the antidiabetic activity of B. purpurea and to cite all the information as a comprehensive article review. Literature was retrieved from Wiley, Science Direct, Springer Link, Google Scholar and Research Gate databases. The antidiabetic activity of this plant was proven by in vitro activities that involve alpha-glucosidase, alpha-amylase and dipeptidyl peptidase IV inhibitory activities. On the other hand, in vivo antidiabetic activity of B. purpurea was carried out using a streptozotocin-induced animal model. Furthermore, the details about the phytochemical constituents present in this plant were collected from various published journals. The literature search discovered that B. purpurea exerts significant antidiabetic activity in both in vitro and in vivo models. In addition, it can be deduced that the significant antidiabetic activity possessed by B. purpurea could be due to various phytochemical constituents such as flavonoids, glycosides and saponins. In conclusion, B. purpurea possesses impressive therapeutic value, which needs to be explored and extended for further studies. Therefore, this review paper opens the door for many researchers to explore further the plant's antidiabetic potential, including the metabolic pathways and the bioactive compounds that could contribute to discovering new drug entities.